PECULIARITIES OF FORMATION OF INFORMATION TECHNOLOGY FOR THE DEVELOPMENT OF INDIVIDUAL TRAJECTORY IN EDUCATIONAL INSTITUTIONS - MIRKO, IHOR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article presents the characteristic features of the formation of information technologies for the development of individual learning, describes the problems and requirements that affect the implementation in the educational process. The purpose of this article is to determine the characteristic features of the formation of information technology for the development of individual learning in educational institutions, which describes the main factors and characteristics in the educational and upbringing processes. During the analysis to determine the characteristics of the formation of information technology for the development of individual trajectory in educational institutions, it was found that information systems play an important role by providing a wide range of tools and resources to improve the effectiveness of educational programmes. It is also found that the formation of information technology for the development of an individual trajectory is ensured by six factors, namely: the use and processing of data, adaptability, interactivity, accessibility, feedback, as well as the use of tools and resources. In accordance with the problem statement, the author describes and analyses the problems of such aspects as limited access to technology, insufficient training and incompetence, financial constraints, heterogeneity of approaches and privacy issues, which together complement each other and create an information system. Thus, the formation and implementation of information technologies for the development of an individual trajectory is an important process for the development of modern education, which may be impossible if: there is no proper training of teaching staff in educational institutions, which complicates the integration of modern technologies into the educational process; limited opportunities due to the insufficient use of modern IT and affects the limited capabilities of students and teachers; if the introduction of IT for personalisation of learning requires significant costs for the purchase of equipment, as well as software.